Extensive Analysis on Generation and Consensus Mechanisms of Clustering Ensemble: A Survey - Yalamarthi Leela Sandhya Rani; V. Sucharita; K. V. V. Satyanarayana (International Journal of Electrical and Computer Engineering (IJECE), 2018)
Data analysis plays a prominent role in interpreting various phenomena. Data mining is the process to hypothesize useful knowledge from the extensive data. Based upon the classical statistical prototypes the data can be exploited beyond the storage and management of the data. Cluster analysis a primary investigation with little or no prior knowledge, consists of research and development across a wide variety of communities. Cluster ensembles are melange of individual solutions obtained from different clusterings to produce final quality clustering which is required in wider applications. The method arises in the perspective of increasing robustness, scalability and accuracy. This paper gives a brief overview of the generation methods and consensus functions included in cluster ensemble. The survey is to analyze the various techniques and cluster ensemble methods.